1995
DOI: 10.1136/jcp.48.3.260
|View full text |Cite
|
Sign up to set email alerts
|

Immunological factors and risk of infection in plateau phase myeloma.

Abstract: Aims-A series of patients with myeloma were investigated to assess whether immunological risk factors predisposing to serious infection could be identified. Methods-Patients (n = 102) with predominantly plateau phase myeloma were monitored prospectively for infections. Immunological parameters including total non-paraprotein immunoglobulins and specific antibody titres were measured in all patients and compared with a control population ofhealthy individuals of a similar age; response to immunisation with Pneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
88
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(97 citation statements)
references
References 15 publications
6
88
1
2
Order By: Relevance
“…Low baseline antibody titers to pneumococci have previously been found in MM patients (20,33) and have been associated with increased risk of serious infection (20). In our study, significantly lower titers were demonstrated in both MM and WM groups than in healthy controls, which fits with the documented susceptibility of these patients to pneumococcal infections (7,23,29).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Low baseline antibody titers to pneumococci have previously been found in MM patients (20,33) and have been associated with increased risk of serious infection (20). In our study, significantly lower titers were demonstrated in both MM and WM groups than in healthy controls, which fits with the documented susceptibility of these patients to pneumococcal infections (7,23,29).…”
Section: Discussionsupporting
confidence: 77%
“…In our study, significantly lower titers were demonstrated in both MM and WM groups than in healthy controls, which fits with the documented susceptibility of these patients to pneumococcal infections (7,23,29). It also highlights the issue of vaccination in these patient groups; however, previous studies on pneumococcal vaccination in MM patients have had discouraging results (20,33). Our control group displayed a high median titer against pneumococci in comparison to adult titers reported in a previous study (34).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…9,10 It has also been shown that multiple myeloma patients display a low immune response to infections and vaccines, and that it also predicted a higher risk of infection. 11,12 In addition to the inherent immunodeficiency, some small studies have described a changing spectrum of infections in MM, possibly related to the more intensive treatment approach of recent years, suggesting that the novel agents may increase the risk of infections in MM patients. [13][14][15][16] Several studies have indicated that elderly MM patients in particular are highly susceptible to infections.…”
Section: Introductionmentioning
confidence: 99%
“…Pneumococcal vaccination is recommended for myeloma patients even though they are known to be poor responders as defined by poor IgG responses postvaccination measured by enzyme-linked immunosorbent assay (ELISA) (1,(10)(11)(12)(13). In a report of a previous study, we stated that pneumococcal vaccination evoked poor responses not only in MM patients but also in elderly patients with WM and MGUS compared to a control group consisting of subjects within the same age range but without hematological disorders (14).…”
mentioning
confidence: 99%